2019
DOI: 10.5603/ep.a2019.0025
|View full text |Cite
|
Sign up to set email alerts
|

BRAF V600E mutation in papillary thyroid cancer is correlated with adverse clinicopathological features but not with iodine exposure

Abstract: Introduction: BRAF V600E activating mutation is the most frequent genetic abnormality in the pathogenesis of papillary thyroid carcinoma. We aimed to evaluate the association between BRAF V600E mutation and well-established prognostic clinicopathological characteristics as well as iodine exposure. Material and methods: From 2000 to 2012, the data of PTC patients admitted to Dr. Lutfi Kirdar Kartal Education and Research Hospital in Turkey were reviewed retrospectively. Clinicopathological parameters were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“… 28 , 29 BRAF V600E mutation was not associated with central lymph node metastasis in PTC patients. 30 In addition, BRAF V600E mutation was associated with age, 31 , 32 advanced tumor stage, 33 , 34 and a reduced prevalence of Hashimoto’s thyroiditis 34 in PTC patients, however, similar results were not obtained in this study.…”
Section: Discussioncontrasting
confidence: 71%
“… 28 , 29 BRAF V600E mutation was not associated with central lymph node metastasis in PTC patients. 30 In addition, BRAF V600E mutation was associated with age, 31 , 32 advanced tumor stage, 33 , 34 and a reduced prevalence of Hashimoto’s thyroiditis 34 in PTC patients, however, similar results were not obtained in this study.…”
Section: Discussioncontrasting
confidence: 71%
“… 8 Previous studies 9 , 10 have reported a strong association between BRAF V600E and the poor clinicopathological outcome of PTCs; however, a paradox has been observed between the high frequency of BRAF V600E mutations in PTCs and the low prevalence of CLNM. 11 13 Hence, controversy remains concerning the value and accuracy of BRAF in predicting CLNM.…”
Section: Introductionmentioning
confidence: 99%
“…B-type Raf (BRAF) kinase mutation on exon 15 is related to the protein kinase pathway and leads to proliferation and metastasis of PTC [ 15 , 16 ]. There are still greatly controversies regarding the value of BRAF gene in predicting cervical CLNM [ 17 , 18 ]. Virk and colleagues have reported PTC patients bearing BRAF mutation were more likely to have cervical CLNM features [ 19 ], but one opposite research documented that BRAF mutation was not a risk factor for CLNM in PTC patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%